A spatial analysis of the Spanish tobacco consumption distribution: Are there any consumption clusters? - Almeida, Alejandro; Golpe, Antonio A.; Martín-Álvarez, Juan Manuel (Public Health, 2020)
Objectives: The objective of this short communication is to provide a previous empirical analysis to locate the regions that have distortions in per capita tobacco consumption. The location of these regions and their proximity to other countries allow us to detect the need that governments have to harmonize policies. Study design: The design of this study is a cross-sectional spatial descriptive analysis. Methods: By using panel data from the 47 Spanish provinces from 2002 to 2017, we implement the Moran's I test which allows us to detect areas where low or high per capita tobacco consumption clusters are generated. Results: The results show that areas of Spain bordering countries with high price differentials, such as Gibraltar and France, generate clusters of low and high per capita tobacco consumption, respectively. Indeed, maintaining a low price differential seems not to generate distortions, as revealed by the Portugal case. Conclusions: Spatial clusters of per capita tobacco consumption are located in regions close to countries where there is high price differential.
Keywords: tobacco; cross-border purchase; price differential; Spain; Scopus; JCR